2023
DOI: 10.3390/ph16020268
|View full text |Cite
|
Sign up to set email alerts
|

Nornidulin, A New Inhibitor of Plasmodium falciparum Malate: Quinone Oxidoreductase (PfMQO) from Indonesian Aspergillus sp. BioMCC f.T.8501

Abstract: This study aimed to obtain a microbial active compound as a novel antimalarial drug from Indonesian isolates. Target-based assays were used to screen for antimalarial activity against the parasite mitochondrial, Plasmodium falciparum malate:quinone oxidoreductase (PfMQO) enzyme. In total, 1600 crude extracts, composed from 800 fungi and 800 actinomycetes extracts, were screened against PfMQO, yielding six active extracts as primary hits. After several stages of stability tests, one extract produced by Aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In general, there are a variety of potent inhibitors, all of which bind to the quinone reaction site in a variety of oxidoreductases that use quinones as substrates. This implies that the quinone-binding site is a possible druggable site in MQO. Using several approaches including drug screening, compounds have been identified that might inhibit MQO. ,,, However, to the best of our knowledge, no inhibitor has been yet reported that interacts with the quinone-binding site. To explore novel inhibitors targeting MQO, it will be necessary to fully understand the mechanism of action of MQO, for example, by solving the structure of enzyme–substrate complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there are a variety of potent inhibitors, all of which bind to the quinone reaction site in a variety of oxidoreductases that use quinones as substrates. This implies that the quinone-binding site is a possible druggable site in MQO. Using several approaches including drug screening, compounds have been identified that might inhibit MQO. ,,, However, to the best of our knowledge, no inhibitor has been yet reported that interacts with the quinone-binding site. To explore novel inhibitors targeting MQO, it will be necessary to fully understand the mechanism of action of MQO, for example, by solving the structure of enzyme–substrate complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Using several approaches including drug screening, compounds have been identified that might inhibit MQO. 12 , 14 , 49 , 50 However, to the best of our knowledge, no inhibitor has been yet reported that interacts with the quinone-binding site. To explore novel inhibitors targeting MQO, it will be necessary to fully understand the mechanism of action of MQO, for example, by solving the structure of enzyme–substrate complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Saponins, on the other hand, possess antimalarial properties by causing erythrocytes to lyse through the destruction of their cell membranes [35,36]. Alkaloids have demonstrated the ability to decrease parasitemia levels by inhibiting the synthesis of parasite DNA and RNA [37]. While steroids and their derivatives have also been found to have antimalarial effects in various studies, the specific mechanism remains unclear.…”
Section: C1 (Negative Control) C2 (Positive Control Receiving Artemis...mentioning
confidence: 99%
“…Malaria eradication has resulted in a decrease in morbidity and mortality [1]. Still, malaria control efforts over the last decade have been ineffective [2]. Malaria control is made worse by the COVID-19 pandemic, which affects the decline and slowdown of care for this infectious disease.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria control is made worse by the COVID-19 pandemic, which affects the decline and slowdown of care for this infectious disease. This condition increased morbidity rates of 240 million cases and a mortality rate of around 627 thousand [2,3]. During the last 20 years, artemisinin combination treatment, or ACT, has been the main medication for treating various malaria infections.…”
Section: Introductionmentioning
confidence: 99%